THE CORRELATION BETWEEN SEX, AGE, NUTRITIONAL STATUS AND DIABETES MELLITUS WITH CLINICAL SYMPTOMS MDR PULMONARY TB AT RSUD DR SOETOMO - Ni Putu Anggita Medyantari; Soedarsono Soedarsono; Manik Retno Wahyunitisari (Universitas Syiah Kuala, 2019)
Abstract. Multi-drug resistance is a condition where drugs rifampicin and isoniazid is not effective in killing bacteria Mycobacterium tuberculosis. Some of the causes of resistance to OAT are the use of a single drug in the treatment of tuberculosis, the use of drugs is inadequate and the irregular drug administration. In RSUD Dr. Soetomo, 25% of MDR Pulmonary TB patients do not want to be treated because symptoms are mild, no pain and feel the treatment is not comparable with the symptoms. This research is to determine the correlation between sex, age, nutritional status and diabetes mellitus with the clinical description of MDR pulmonary TB patients in RSUD Dr. Soetomo. Hence, it is expected people can make the earliest possible prevention against this disease. In addition, clinicians are more aware of the symptoms of MDR Pulmonary TB. Method in this research is descriptive observational study research. There were 103 patients taken as the sample of the study. Research variables consist of sex, age, nutritional status, and diabetes mellitus. The obtained data were analyzed by administering Chi- square analysis. The results of this study showed that each variable tested in this study (sex, age, nutritional status and diabetes mellitus) associated with the symptoms of MDR Pulmonary TB has p 0.05 which means no significant relationship. There are no relation between sex, age, nutrition status and comorbidities with symptom of MDR pulmonary TB. Keywords: multidrug resistance, sex, age, nutritional status, diabetes mellitus Multi-drug resistance adalah suatu kondisi dimana obat rifampisin dan isoniazid tidak efektif dalam membunuh bakteri Mycobacterium tuberculosis. Beberapa penyebab resistensi terhadap OAT adalah penggunaan obat tunggal dalam pengobatan tuberkulosis, penggunaan obat tidak memadai dan pemberian obat tidak teratur. Di RSUD Dr. Soetomo, 25% pasien TB paru MDR tidak mau diobati karena gejalanya ringan, tidak terasa sakit dan rasakan pengobatannya tidak sebanding dengan gejalanya. Penelitian ini bertujuan untuk mengetahui hubungan antara jenis kelamin, umur, status gizi dan diabetes mellitus dengan gambaran klinis pasien TB paru MDR di RSUD Dr. Soetomo. Sehingga diharapkan masyarakat bisa melakukan pencegahan paling dini terhadap penyakit ini. Selain itu, dokter lebih sadar akan gejala TB paru MDR. Metode yang digunakan dalam penelitian ini adalah penelitian observasional deskriptif. Terdapat 103 pasien yang diambil sebagai sampel penelitian. Variabel penelitian terdiri dari jenis kelamin, umur, status gizi, dan diabetes mellitus. Data yang diperoleh dianalisis dengan analisis Chi-square. Hasil penelitian ini menunjukkan bahwa setiap variabel yang diuji (jenis kelamin, usia, status gizi dan diabetes mellitus) yang dihubungkan dengan gejala TB paru MDR memiliki p 0,05 yang berarti tidak ada hubungan yang signifikan. Kesimpulannya, tidak ada hubungan antara jenis kelamin, usia, status gizi dan komorbiditas dengan gejala TB paru MDR.